Abstract 006: Glenzocimab Is Associated With Less Haemorrhagic Transformation Using Artificial Intelligence Imaging In Mechanical Thrombectomy Patients - Andrea Comenducci; Adeline Meilhoc; Yannick Pletan; Sophie Binay; Gilles Avenard; Davide Carone; Alistair Perry; Rafael Namias; Olivier Joly; George Harston; Mikael Mazighi (Stroke: Vascular and Interventional Neurology)
Introduction Lesion volume measurement provides an objective and quantitative assessment of stroke severity and it is often used as a surrogate endpoint of clinical outcome in therapeutic trials. ACTIMIS (NCT03803007) was a randomized phase 1b/2a clinical trial evaluating glenzocimab, a monoclonal antibody fragment targeting platelet receptor glycoprotein VI, versus placebo in patients with acute ischemic stroke treated by thrombolysis alone or associated with mechanical thrombectomy (MT), both subgroups being well balanced. Primary analysis demonstrated a significant reduction in intracranial hemorrhage occurrence stroke‐related mortality and a trend towards reduction in severe disability. In this sub‐analysis, Artificial Intelligence (AI) imaging biomarkers were used to assess efficacy of glenzocimab in the subgroup undergoing MT in the pooled phase 1b (dose escalation) and phase 2a (dose confirmation) studies. Methods In the phase 1b study, patients were randomized to an escalating dose of glenzocimab or placebo (4:1, n=12 per group, 125mg, 250mg, 500mg, 1000mg). In the phase 2 dose confirmation study, patients were randomized (1:1) with 1000mg glenzocimab or placebo. CT scan or MRI was acquired at baseline with CT at 24 hours and MRI at 7 days (CT if MRI not available) for safety and efficacy analysis, respectively. Baseline and follow up imaging were processed using Brainomix software (Oxford, UK). AI output was reviewed for accuracy by an expert clinician (DC) blinded to treatment allocation. Results Of 166 patients in the trial, 81 patients underwent MT and had follow up non‐contrast CT imaging available at 24 hours (48 glenzocimab, 33 placebo) and 72 had Day‐7 imaging (47 glenzocimab, 25 placebo). Day‐7 imaging was available for 8 fewer placebo patients and 1 glenzocimab patient than at 24 hours. All except 2 patients (1 placebo, 1 glenzocimab) with missing data at Day‐7 died during the study. Multivariate regression modelling showed a significant interaction between patients undergoing MT and receiving glenzocimab. Glenzocimab had a greater effect on reducing the risk of haemorrhagic transformation in the MT subgroup (exploratory p=0.001). Presenting acute infarct volume was similar between glenzocimab and placebo arms (mean [SD]; 16.27mL [30.2] vs. 19.62mL [28.98], non‐significant). There was a significantly smaller volume of haemorrhagic transformation in the glenzocimab group at 24 hours compared to placebo (1.83mL [6.59] vs 33.46mL [75.07], exploratory p<0.01) and a trend towards smaller volume of ischemic injury in the glenzocimab group (52.32mL [82.07] vs 62.93mL [79.4]). Similar significant trend at Day‐7 for haemorrhagic transformation was seen but less marked due to the unbalanced loss to follow up at Day‐7 (2.99mL [12.35] vs 4.19mL [10.83], exploratory p<0.05). Conclusion Glenzocimab reduces likelihood of haemorrhagic transformation in patients undergoing MT. Haemorrhage volumes were smaller in the glenzocimab group and encouragingly there was a trend to smaller volumes of ischemic injury. There was a greater drop‐out rate in the placebo group between 24 hours and Day‐7, which resulted in a smaller difference in haemorrhagic volumes at Day‐7. Those results, which are to be further analysed in ACTIMIS overall population of AIS patients, could highlight glenzocimab mechanism in the reperfusion injury mitigation.